Modern Methods of Teaching Monologue and Dialogue Speech in Foreign Language - Uktamovna, Buranova Lola (Researchparks Publishing, 2023)
The article analyzes the specifics of monologue and dialogue speech and considers the problem of teaching this type of speech activity of students in foreign language classes. Particular attention is paid to the levels and parameters.